G286(P) Audit of virtual orthopaedic consultation from paediatric accident and emergency through e-folder. (24th May 2017) - Natarajan, U; Gilbert, J; Gardner, S
Abstract : Aims: Difficulties in communication between Orthopaedic on call and Paediatric Accident and Emergency (A and E) clinicians due to split site, prompted virtual consultation via e-folder. (Orthopaedic doctor not available on Paediatric A and E site to review patient; senior orthopaedic input not available for all patients) A shared orthopaedic e-folder, set up as an iterative Quality improvement programme to facilitate and streamline orthopaedic referrals from Paediatric A and E, was reviewed. Was the process safe? Demographic profile of children referred Outcome of referral Methods: Paediatric A and E clinician inputs into the shared folder (set up as columns), patient demography, mechanism and nature of injury, clinical findings. These details along with X-ray are reviewed in Orthopaedic consultant-led trauma meeting following day and management plan communicated via e-folder, which is actioned by Paediatric A and E clinician by 9 AM. The e-folder data were analysed retrospectively for a 12 month period of January to December 2015. Results: 283 children were referred for virtual consultation through shared e-folder (1% A and E attendances). Date of birth of patient was missing in six; name and GMC/NMC number of clinician was available only in 38.9%. 161 cases (57%) were discussed over the phone with orthopaedic on call in addition to ereferral. Orthopaedic referrals peaked during June – October. Radius, radius and ulna, humerus, and elbow fractures were most common. Trauma meeting outcome: 192 cases were reviewed in fracture clinic within one week. Surgery was planned in 40 (manipulation under anaesthesia alone or plus K-wire/ORIF); 40 cases needed other procedures/conservative management; outcome was not recorded in 11 cases. Tertiary centre consultation/ referral was made in 9 cases only. Conclusion: Clinical information provided in the folder (columns) was adequate in streamlining referrals. Documentation was good. Recording of name, GMC number of Paediatric A and E/Orthopaedic clinician requires improvement. Understanding demographics will help in arranging targeted services and education. Majority of cases were dealt with locally, only a few requiring tertiary hospital consultation/referral. Virtual consultation via shared folder has shown to be an effective quality improvement programme in a setting of split site services. It provides consultant-led decisions in a timely fashion for all children referred.